A quadratic polynomial P ( x ) satisfies P ( x 3 + x ) ≥ P ( x 2 + 1 ) for all real numbers x .
Find the sum of the roots of P ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let P ( x ) = a x 2 + b x + c , and y = P ( x 3 + x ) − P ( x 2 + 1 ) .
We need to find the value of a − b .
It is easy to get y = P ( x 3 + x ) − P ( x 2 + 1 ) = a ( x 2 + 1 ) 2 ( x 2 − 1 ) + b ( x 2 + 1 ) ( x − 1 ) ≥ 0 .
Let b = k a for some real number k . Therefore, y = a ( x 2 + 1 ) 2 ( x 2 − 1 ) + k a ( x 2 + 1 ) ( x − 1 ) = a ( x 2 + 1 ) ( x − 1 ) [ ( x 2 + 1 ) ( x + 1 ) + k ] .
WLOG a ≥ 0 . We got y = a ( x 2 + 1 ) ( x − 1 ) [ ( x 2 + 1 ) ( x + 1 ) + k ] ≥ ( x − 1 ) [ ( x 2 + 1 ) ( x + 1 ) + k ] .
Let Q ( x ) = ( x 2 + 1 ) ( x + 1 ) + k = R ( x ) + k
(i) First Case : x = 0 , y = 0
(ii) Second Case : x > 1 , y ≥ Q ( x ) .
(iii) Third Case : When x < 1 , Q ( x ) has to be negative in order for the original inequality to be satisfied.
It is obvious that Q ( 1 ) = R ( 1 ) + k = 4 + k and R ( x ) is a monotonically increasing function. Therefore R ( m ) ≤ 4 ∀ m ≤ 1 . Thus, Q ( x ) = R ( x ) − 4 < 0 ∀ x < 1 , satisfying the third case.
Again, R ( x ) is monotonically increasing, therefore R ( m ) > 4 ∀ m > 1 . Therefore Q ( x ) > 0 ∀ x > 1 . Satisfying the second case. It implies that k = − 4 satisfies all the case.
Thus, b = k a = − 4 a , implying a − b = 4 .
Thus the sum of the roots of P ( x ) is equal to 4.
Great solution!
Here is a interesting way to look towards the problem, x^2+1 > 1 1. Let x>1 x^2+1>2 x(x^2 + 1) > x^2 + 1 > 2 2. Let 0<x<1 1< x^2 + 1< 2 0<x(x^2+1)<x^2+1<2 therefore at 2 the minima of parabola occur hence sum of roots/2 = 2
Problem Loading...
Note Loading...
Set Loading...
I posted the solution to this question on Art of problem solving a while ago, so I am going to copy paste it instead of typing again.
Solution :
Let P ( r ) = a r 2 + b r + c → Sum of roots = a − b
For simplicity, x 3 + x = t & x 2 + 1 = q
∴ P ( t ) ≥ P ( q )
∴ a t 2 + b t + c ≥ a q 2 + b q + c
a ( t 2 − r 2 ) + b ( t − r ) ≥ 0
( t − r ) ( a ( t + r ) + b ≥ 0
( x 3 − x 2 + x − 1 ) ( a ( x 3 + x 2 + x + 1 ) + b ) ≥ 0 x ∈ R
( x 2 + 1 ) ( x − 1 ) ( a ( x 2 + 1 ) ( x + 1 ) + b ) ≥ 0 for all x ∈ R
∴ ( x − 1 ) ( a ( x 2 + 1 ) ( x + 1 ) + b ) ≥ 0 for all x ∈ R
For x > 1,
a ( x 2 + 1 ) ( x + 1 ) + b ≥ 0
For x < 1 a ( x 2 + 1 ) ( x + 1 ) + b ≤ 0
Thus, equality holds for one, i.e x = 1 is a root of ( a ( x 2 + 1 ) ( x + 1 ) + b )
∴ a ( 2 ) ( 2 ) + b = 0
∴ a − b = 4
Thus, the sum of roots of P ( r ) is 4